Fropofol decreases force development in cardiac muscle. Issue 8 (9th March 2018) - Ren, Xianfeng; Schmidt, William; Huang, Yiyuan; Lu, Haisong; Liu, Wenjie; Bu, Weiming; Eckenhoff, Roderic; Cammarato, Anthony; Gao, Wei Dong
Abstract : Supranormal contractile properties are frequently associated with cardiac diseases. Anesthetic agents, including propofol, can depress myocardial contraction. We tested the hypothesis that fropofol, a propofol derivative, reduces force development in cardiac muscles via inhibition of cross‐bridge cycling and may therefore have therapeutic potential. Force and intracellular Ca 2+ concentration ([Ca 2+ ]i ) transients of rat trabecular muscles were determined. Myofilament ATPase, actin‐activated myosin ATPase, and velocity of actin filaments propelled by myosin were also measured. Fropofol dose dependently decreased force without altering [Ca 2+ ]i in normal and pressure‐induced hypertrophied‐hypercontractile muscles. Similarly, fropofol depressed maximum Ca 2+ ‐activated force (Fmax ) and increased the [Ca 2+ ]i required for 50% of Fmax (Ca50 ) at steady state without affecting the Hill coefficient in both intact and skinned cardiac fibers. The drug also depressed cardiac myofibrillar and actin‐activated myosin ATPase activity. In vitro actin sliding velocity was significantly reduced when fropofol was introduced during rigor binding of cross‐bridges. The data suggest that the depressing effects of fropofol on cardiac contractility are likely to be related to direct targeting of actomyosin interactions. From a clinical standpoint, these findings are particularly significant, given that fropofol is a nonanesthetic small molecule that decreases myocardial contractility specifically and thus may be useful in the treatment of hypercontractile cardiac disorders.—Ren, X., Schmidt, W., Huang, Y., Lu, H., Liu, W., Bu, W., Eckenhoff, R., Cammarato, A., Gao, W. D. Fropofol decreases force development in cardiac muscle. FASEB J . 32, 4203‐4213 (2018). www.fasebj.org